Kontribusi Kekuatan Otot Kaki, Keseimbangan terhadap hasil passing sepak bola SSB Banteng Muda Duminanga - Akmal Nuhia; Juni Isnanto; Mohamad Reza Pratama Diuli (Jambura Arena Sport, 2026)
The study aims to analyze the contribution of leg muscle power and balance to soccer passing ability in players of SSB Banteng Muda Duminanga. A quantitative approach with a correlational design was used. The independent variables were leg muscle power (X1) and balance (X2), while the dependent variable was soccer passing performance (Y). The population consisted of 42 players, with a sample of 30 selected through purposive sampling based on training participation. Instruments included the standing broad jump test for leg muscle power, the stork stand test for balance, and the passing and stopping test for passing ability. The results showed that: (1) leg muscle power correlated with passing performance (r = 0.62) with a contribution of 39.32%; (2) balance correlated with passing performance (r = 0.75) contributing 56.79%; and (3) combined, leg muscle power and balance had a very strong relationship with passing performance (r = 0.99) with a contribution of 99.83%. These findings indicate that leg muscle power and balance are crucial physical condition factors for enhancing soccer passing ability. Coaches and trainers should prioritize developing both attributes in training programs to optimize players’ passing performance